Comparison of Late Neogene Uk′37 and TEX86 Paleotemperature Records From the Eastern Equatorial Pacific at Orbital Resolution. Issue 7 (30th June 2020) - Lawrence, K. T.; Pearson, A.; Castañeda, I. S.; Ladlow, C.; Peterson, L. C.; Lawrence, C. E.
Abstract: Key features of late Neogene climate remain uncertain due to conflicting records derived from different sea surface temperature (SST) proxies. To understand scenarios in which proxy‐derived temperature estimates can be used interchangeably or are instead measuring different aspects of the same system, it is necessary to explore both the consistencies and differences between specific paleothermometers. Here, we report orbital‐scale climate records from ODP Site 846 in the eastern equatorial Pacific (EEP) for the interval from 5–6 Ma using alkenone and archaeal lipid paleothermometers. Results from both proxies are similar in their secular trends and magnitude of long‐term temperature change, and spectral analysis demonstrates that the records are coherent and in‐phase in both the obliquity and precession bands. However, we find that the temperatures reconstructed by TEX86 are consistently offset toward colder values by 2 °C relative to U k′ 37 ‐derived temperatures in global calibrations, or by 0.8 °C in Bayesian‐based calibrations. All combinations of calibrations also yield approximately twice the amplitude of orbital‐scale variation in TEX86 relative to U k′ 37 ‐derived temperature fluctuations. Both temperature proxies are negatively correlated with sedimentary alkenone concentrations, which we use as an indicator of increased export productivity. Removing this productivity contribution from TEX86 results in an adjusted TEX86 record with temperature sensitivity identical to U k′ 37 . In future applications, this signal may be decoupled using additional sedimentary indicators of paleoproductivity, which likely will be most important for upwelling zone environments. There remain other nonexplained factors that contribute to differences between TEX86 and U k′ 37 that warrant additional investigation. Plain Language Summary: The remains of organisms found in ocean sediments contain information about the climate at the time the organisms were alive. Some of these remains enable the reconstruction of past temperature and are used as "paleothermometers." Many different types of paleothermometers exist; however, none work across all time periods or geographic locations. Thus, data from different paleothermometers are commonly used interchangeably to study Earth ' s past climate. However, little previous work has been done to study the limitations of this approach. Two of the most widely used paleothermometers are based on lipids of marine microorganisms. Here, we generated high‐resolution temperature reconstructions using both techniques. This allowed us to compare the timing, direction, and magnitude of the reconstructed temperature changes over a time interval of nearly 1 million years. Encouragingly, both paleothermometers show the same general patterns through time, although they yield modestly different results. These differences are greater during cold climate conditions and appear to be in part due to the influence of the amount of local biological productivity on one of the paleothermometers. We propose some ways that the contribution of factors other than temperature, including not only productivity but also community composition, might be explored in the future. Key Points: Orbital‐resolution U k′ 37 and TEX86 paleotemperature records are coherent and in‐phase in the late Neogene eastern equatorial Pacific Regardless of calibration choice, archaeal lipid records yield colder temperatures with larger‐amplitude variations than alkenone records Temperature and productivity explain half the variance between U k′ 37 and TEX86 records; other unconstrained factors warrant exploration